CD8‐positive pseudolymphoma in lues maligna and human immunodeficiency virus with monoclonal T‐cell receptor‐beta rearrangement. (10th December 2018) - Mitteldorf, Christina; Plumbaum, Heidi; Zutt, Markus; Schön, Michael P.; Kaune, Kjell M.
Abstract : A 42‐year‐old Caucasian man suffered from disseminated plaques and ulcerated nodules for 6 weeks. He had weight loss and generalized lymphadenopathy. Underlying diseases were not known up till then. Based on a skin biopsy, the diagnosis of CD8‐positive cutaneous T‐cell lymphoma, type mycosis fungoides was made in a pathological reference center for lymphoma. A reproducible T‐cell receptor (TCR)‐beta rearrangement was detectable. Before starting therapy, a new biopsy was taken and the previous diagnosis was re‐evaluated taking clinical images and symptoms into account. Based on both, the diagnosis of a CD8+ pseudolymphoma in lues maligna and human immunodeficiency virus was made. We highlight histopathologic clues for the correct diagnosis, and we emphasize the indispensability of clinical‐pathological correlation. Furthermore, we discuss the differential diagnosis of CD8+ lymphoproliferative disorders.